Immunoglobulin for Polyneuropathy - J Gordon Millichap (Pediatric Neurology Briefs, 1990)
The value of high-dose intravenous immunoglobulin in the treatment of chronic inflammatory demyelinating polyneuropathy was studied in a double-blind, placebo controlled, crossover investigation at the Department of Neurology, University Hospital Rotterdam-Dijkzigt, the Department of Immunohematology and Bloodbank, University Hospital Leiden, and the Central Laboratory of the Netherlands, Red Cross Blood Transfusion Service, Amsterdam, The Netherlands.